2021
DOI: 10.3389/fphy.2021.741453
|View full text |Cite
|
Sign up to set email alerts
|

Development and Benchmarking of a Monte Carlo Dose Engine for Proton Radiation Therapy

Abstract: Dose calculation algorithms based on Monte Carlo (MC) simulations play a crucial role in radiotherapy. Here, the development and benchmarking of a novel MC dose engine, MonteRay, is presented for proton therapy aiming to support clinical activity at the Heidelberg Ion Beam Therapy center (HIT) and the development of MRI (magnetic resonance imaging)-guided particle therapy. Comparisons against dosimetric data and gold standard MC FLUKA calculations at different levels of complexity, ranging from single pencil b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…In particle therapy, inelastic nuclear scattering events generate the mixed radiation field, that is, photons, protons, neutrons, deuterons, tritons, 3 He particles, helium ions ( 4 He) and heavier fragments (nuclear recoils). For the handling of proton beams, photons and neutrons were assumed to be dosimetrically irrelevant and they were neither transported nor produced 16 . To verify that the same could be applied for helium ion beams, FLUKA simulations were run for an energy range of 50−220 MeV/u, and it was found that the contribution of photons and neutrons to the integrated depth dose distribution in water was smaller than 0.03% and therefore they are also neglected for helium ion beams.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particle therapy, inelastic nuclear scattering events generate the mixed radiation field, that is, photons, protons, neutrons, deuterons, tritons, 3 He particles, helium ions ( 4 He) and heavier fragments (nuclear recoils). For the handling of proton beams, photons and neutrons were assumed to be dosimetrically irrelevant and they were neither transported nor produced 16 . To verify that the same could be applied for helium ion beams, FLUKA simulations were run for an energy range of 50−220 MeV/u, and it was found that the contribution of photons and neutrons to the integrated depth dose distribution in water was smaller than 0.03% and therefore they are also neglected for helium ion beams.…”
Section: Methodsmentioning
confidence: 99%
“…For the handling of proton beams, photons and neutrons were assumed to be dosimetrically irrelevant and they were neither transported nor produced. 16 To verify that the same could be applied for helium ion beams, FLUKA simulations were run for an energy range of 50−220 MeV/u, and it was found that the contribution of photons and neutrons to the integrated depth dose distribution in water was smaller than 0.03% and therefore they are also neglected for helium ion beams. Like the elastic cross section, the total inelastic cross sections of helium ions are tabulated from 0.1 MeV/u to 500.1 MeV/u, however they are tabulated for all ten elements inside MonteRay, and not just for hydrogen.…”
Section: Inelastic Nuclear Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have been studied in some detail for a range of field strengths and configurations [89,[92][93][94]. Dedicated dose calculation algorithms for proton therapy have been proposed, which can enable substantial speed ups in dose calculation time without compromising accuracy [95]. The effect of magnetic fields on secondary electrons is smaller than in MRI-Linac therapy, as the energy of secondary electrons created by particle beams is lower [89,92] whilst the perturbation of proton trajectories in the patient is deterministic and can be handled with inverse planning.…”
Section: Physics Challenges For Design Of Mri-proton Systems 41 Choic...mentioning
confidence: 99%
“…Many of these tools are in use clinically at affiliated sites, and additionally, aspects of PyMedPhys are implemented around the world for some applications. Many parties have embraced the gamma analysis module (Castle et al, 2022;Cronholm et al, 2020;Gajewski et al, 2021;Galić et al, 2020;Lysakovski et al, 2021;Milan et al, 2019;Pastor-Serrano & Perkó, 2021;Rodrıǵuez et al, 2020;Spezialetti et al, 2021;Tsuneda et al, 2021;Yang et al, 2022), while implementations of the electron cutout factor module and others (Baltz & Kirsner, 2021;Douglass & Keal, 2021;Rembish, 2021) have also been reported. Additionally, the work has been recognized by the European Society for Radiotherapy and Oncology (ESTRO) and referenced as recommended literature in their 3rd Edition of Core Curriculum for Medical Physics Experts in Radiotherapy (Bert et al, 2021).…”
Section: Statement Of Needmentioning
confidence: 99%